Two new species of resupinate poroid fungi (Basidiomycota, Polyporaceae) from São Tomé and Príncipe Archipelago - Melo, Ireneia; Salcedo, Isabel; Garcia, Cesar A.; Olariaga, Ibai (Phytotaxa, 2023)
Megasporia insularis and Porogramme principes are described as new species based on morphological and molecular data of specimens collected on the Island of Príncipe (São Tomé and Príncipe Archipelago). Megasporia insularis is characterized by the hymenophore with large regular pores, a di-trimitic hyphal system with strongly dextrinoid skeletal hyphae, apically acuminate hyphal endings at the dissepiments edges, presence of dendrohyphidia, and large, subcylindrical basidiospores. Our phylogenetic analyses of the ITS-nLSU-mtSSU-RPB1-RPB2-TEF regions support the placement of M. insularis within an inclusive clade containing the redefined Megasporia. Porogramme principes has small irregular pores, a dimitic hyphal system with weakly dextrinoid skeletal hyphae, and small, oblong-ellipsoid basidiospores. The phylogenetic analyses of Porogramme and related genera place P. principes, together Grammothele taiwanensis, in a supported clade sister to P. subargentea, and separate from the species clade Grammothele s.str. Therefore, we propose to combine the species G. taiwanensis as Porogramme taiwanensis. Illustrations of these two novel species and updated keys to Megasporia and Porogramme genera are provided.